Класифікація зображень за частковим поданням - Рибалка, М. О. (ХНУРЕ, 2023)
A method of image classification based on a set of key point descriptors is discussed. Modeling was carried out for the situation of analysis of an incomplete description. A comparison of data search results with hashingand without hashing was made.
Keywords: класифікація зображень, дескриптори ключових точок